The Role of Inflammatory Cytokines and lncRNAs in the Pathogenesis of Atherosclerosis and Other Inflammatory Diseases: Focus on Sarcoidosis and Alzheimer’s Disease - Sokołowska, Aldona; Buszek, Julia; Czerniak, Piotr; Antoszewska, Adrianna; Bargiel, Weronika; Bąk, Dominika; Wajdowicz, Halszka; Warzocha, Mateusz (Quality in Sport, 2025)
Introduction Atherosclerosis, a chronic inflammatory disease of the arterial wall, remains a leading cause of morbidity and mortality worldwide. Recent advances highlight the role of inflammatory cytokines and long non-coding RNAs (lncRNAs) in its pathogenesis. Aim of the Study This study synthesizes current knowledge on the interplay between cytokines and lncRNAs across these conditions, emphasizing their potential as biomarkers and therapeutic targets. Materials and Methods Through a systematic review of recent studies, we identify key pathways and discuss translational implications for novel interventions. Description of the State of Knowledge Inflammatory cytokines, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6), orchestrate immune responses that exacerbate endothelial dysfunction, foam cell formation, and plaque instability. Concurrently, lncRNAs regulate gene expression through transcriptional and post-transcriptional mechanisms, influencing cellular processes such as macrophage polarization and smooth muscle cell proliferation. Beyond atherosclerosis, these mediators are implicated in the pathogenesis of other inflammatory diseases, including sarcoidosis and Alzheimer’s disease. Conclusion Our findings underscore the critical need for integrated approaches targeting both inflammatory mediators and epigenetic regulators to mitigate the burden of these diseases.